Study the effect of aqueus extract Alhagi maurorum on estrogen Changes during the Reproductive Cycle in Local Female Rabbits (Sebha University Conference Proceedings, 2024)
In order to investigate the effect of aqueous extract of the Alhagi maurorum on the estrogen hormone changes during the reproductive cycle in local female rabbits, this study was conducted at the Sabha Agricultural Project from 1/12/2022 to 15/01/2023. The animals were left for two weeks for adaptation to the experimental conditions. The experiment was designed using 25 local female rabbits, divided into 5 groups, with each group consisting of 5 females. The first group was used as a control group. The second group was given the aqueous extract of Alhagi maurorum roots at a concentration of 1 ml, while the third group was given the aqueous extract of Alhagi maurorum  roots at a concentration of 3 ml. The fourth group was administered the aqueous extract of the aerial part of the Alhagi maurorum at a concentration of 1 ml, and the fifth group was administered the aqueous extract of the aerial part of the Alhagi maurorum at a concentration of 3 ml. Blood samples were collected from the treatment groups three times, at an interval of 10 days, while a single sample was taken from the control group for comparison with the treatments. The results of the statistical analysis showed a significant increase in estrogen hormone levels in the groups treated with the aqueous extract of Alhagi maurorum roots at concentrations of 1 ml and 3 ml, compared to the control group and the group that used the aqueous extract of the aerial part of the Alhagi maurorum